A review of the extraction and purification methods, biological activities, and applications of active compounds in Acanthopanax senticosus - Zhang, Xindi; Guan, Lijun; Zhu, Ling; Wang, Kunlun; Gao, Yang; Li, Jialei; Yan, Song; Ji, Nina; Zhou, Ye; Yao, Xinmiao; Li, Bo (Frontiers in Nutrition, 2024)
Acanthopanax senticosus (AS) is a geo-authentic crude medicinal material that grows in China, Korea, Russia, and Japan. AS contains bioactive compounds such as eleutherosides, polysaccharides, and flavonoids. It is also a key traditional herb in the Red List of Chinese Species. AS is mainly distributed in northeast China, such as the provinces of Heilongjiang, Jilin, and Liaoning. It has significant biological activities, including neuroprotective, antioxidant, anti-fatigue, and antitumor activities, which are associated with its active compounds. However, the extraction methods of active compounds are complex, the extraction efficiency is poor, and the structure-activity relationship is unclear. This study focused on the nutrients in AS, including protein, carbohydrates, lipids, etc. Particularly, the active ingredients (eleutherosides, polysaccharides, and flavonoids) in AS and their extraction and purification methods were analyzed and summarized herein. The biological activities of extracts have been reviewed, and the mechanisms of anti-oxidation, antitumor, anti-inflammation, and other activities are introduced in detail. The applications of AS in various domains, such as health foods, medicines, and animal dietary supplements, are then reported. Compared with other extraction methods, ultrasonic or microwave improves efficiency, yet they can damage structures. Challenges occur in recovery of solvent and achieving extraction efficiency when using green solvents, such as deep eutectic solvents. Improvements can be made by combining extraction methods and controlling conditions (power, temperature, time). Bioactive molecules and related activities are exposited clearly. The applications of AS have not been widely popularized, and the corresponding functions require further development.